The comparison results of the electron beam depth dose distribution formed by standard and 3d-printed boluses - Bushmina E. A. Elizaveta Alekseevna; Bulavskaya A. A. Angelina Aleksandrovna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2023, 2023)
Текстовый файл